The Legal Status of Gig Economy Workers in Indonesia's Digital Platform Industry (2022-2025): Problematika Status Hukum Pekerja Gig Economy dalam Industri Platform Digital Indonesia (2022-2025) - Wardhana, Adi Pratomo Kusuma; Rasji, Rasji (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid expansion of Indonesia’s digital economy during 2022–2025 has intensified the reliance on gig-based labor across transportation, logistics, and on-demand services. Specific Background: Despite their substantial contribution, gig workers’ legal standing remains ambiguous because platform companies categorize them as “partners” while exercising algorithmic control resembling conventional employment. Knowledge Gap: Existing Indonesian labor regulations have not adapted to digital platform work, leaving uncertainty regarding worker rights, social protection, and dispute-resolution mechanisms. Aims: This study analyzes the legal status of gig workers in Indonesia’s platform industry and examines the legal problems arising from the absence of explicit regulatory recognition. Results: Findings show that gig workers fulfill substantive elements of employment—work, wage, and command—yet remain excluded from protections related to minimum income, social security, occupational safety, and industrial dispute settlement. Novelty: This research provides a comprehensive doctrinal analysis demonstrating that algorithmic management constitutes a form of digital subordination, positioning gig workers within disguised employment relationships under Indonesian labor law. Implications: Regulatory reform is urgently required to establish clear employment categories, ensure fair protection standards, and align national policy with global trends in safeguarding platform workers. Highlights: Gig workers exhibit substantive employment elements despite being labeled as partners. Algorithmic management creates digital subordination and economic dependency. Regulatory gaps leave gig workers without adequate social, wage, and dispute-resolution protections. Keywords: Gig Economy, Platform Work, Legal Status, Algorithmic Control, Labor Protection